(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article is dedicated to the description of the impact of sects or new religious trends on the politico-social life of Western European countries. The main attention was paid to the role and activities of sects or new religious trends in a contemporary society in the context of globalization. Also several types of classification of sects were considered from historical, psychological, cultural, intellectual points of view. The functioning of these organizations was explored with accordance to the particular period of time in the history of these countries. The important documents which were adopted as the inseparable part of activities which were directed to combating harmful effects and regulation or stabilization of the general problems occurred due to the activities of sects were examined and described. Works of international and local organizations which are responsible for regulating situation established around these organizations were critically reviewed. Not only religious aspect of these organizations but also economic, political, social, psychological aspects were described with the assistance of exact facts and real situations. Resolute and uncertain decisions or actions against the real threat which was caused due to the activities of the sects were portrayed on the example of particular countries. The main goals and objectives of sects which are usually hidden under the veil of religiosity and moral demands were exposed in their full and real essence. Also difficulties and obstacles which occurred while the adoption of strict measures against the sects because of the secular nature of Western European counties were described. Key words: sects, new religious trends, classifications, violence, psyche, reports, recommendations, laws, measures.